Biaxial cyclic loading of woven fabrics - Brnada, Snježana; Kovačević, Stana; Šabarić, Irena; Držaić, Lovro (2021)
For the purpose of this paper, investigations were carried out on specifically designed fabrics with different structural parameters. The biaxial cyclic loading of fabrics and its consequences were investigated. The weave structures with the smallest weave units (plain weave, basket weave 2/2, rib weave 1/1 (2+2) and rib weave 2/2 (1+1) with the same warp and weft density (24 ends/cm and 24 picks/cm) were selected. Biaxial cyclic loadings of fabrics were performed on a newly developed patented device. The influence of the low level of cyclic loadings of fabrics on the change of tensile properties in warp and weft direction was investigated. The results showed that the low level of biaxial cyclic loading can lead to a permanent linear deformation of fabrics. Despite the fact that the forces that cyclically strain the fabric in two directions amount to 10% of the breaking elongation, after a certain number of cycles there is an irreversible deformation and reduction of breaking forces, but sometimes they can result in an increase in breaking forces. It was found that the tensile elongation of fabrics is affected both by thread crimping and by the structural properties of fabrics resulting from changes in the weave.
Bibliografija: 22 jed.
Abstract.
Keywords: Tkanine -- Cikličko opterećenje -- Deformacije -- Vlačno naprezanje